Rudiments de parler chinois: dialect du [Ho Kien Fu] - Wieger, Léon (Imprimerie de la Mission catholique, 1899)
Keywords: 10.Cover Damage; 2.Damage; China; Chinese language; Chinese language Readers; Chinese literature; Chinese literature Translations into French; Condition: Fair; French literature Translations from Chinese; Readers (Publications); Translations; languages

Rudiments de parler chinois: dialect du [Ho Kien Fu] - Wieger, Léon (Imprimerie de la Mission catholique, 1899)
《汉语入门》（Rudiments de Parler Chinois: Dialecte Du）是法国耶稣会士戴遂良（Léon Wieger，1856-1933）以清末河间府方言为基础编写的汉语口语教材。该书共两册，分别于 1895 和 1899 年出版，是作者计划出版的十二卷本丛书“汉语汉文入门” 的第一卷（刘亚男，2017）。戴遂良于 1887 年来华，1933 年逝世于献县。在华 46 年间，他一直在直隶献县教区传教，一生绝大多数时间都居住在献县，仅 1911 年离开中国出行日本和欧洲。1905 年，根据沙畹的提名，戴遂良的《汉语入门》获得法国汉学研究最高奖项——儒莲奖。1919 年，他被巴黎国际历史学协会评为“最有影响的汉学家”之一（谢海涛，2013）。
Keywords: 10.Cover Damage; 2.Damage; China; Chinese language; Chinese language Readers; Chinese literature; Chinese literature Translations into French; Condition: Fair; French literature Translations from Chinese; Readers (Publications); Translations; languages